Pengaruh Live Shopping, Online Review, Persepsi Harga dan Gratis Ongkir Terhadap Minat Beli Konsumen Muslim Kabupaten Pekalongan di Aplikasi Shopee - Muhammad Ilham Maulana; Rinda Asytuti (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Live shopping, online reviews, price perception and shipping discounts are features released by the e-commerce platform Shopee. This feature aims to attract consumer buying interest. Ease of shopping will be one of the buying interests of consumers, especially Muslim consumers in Pekalongan district. This research aims to test the influence of Live shopping, online reviews, price perceptions and postage discounts on Muslim consumers' buying interest in the Shopee application, especially in Pekalongan Regency.This research is a type of quantitative research. The data collection method in this research is the questionnaire method using a sample of 96 respondents. The sampling technique uses the Accidental sampling method. This research uses multiple linear regression test data analysis with the help of SPSS 24.0. The research results show that live shopping, online reviews, price perceptions and postage discounts have a positive effect on Muslim consumers' buying interest in the Shopee application. Then simultaneously Live shopping, online reviews, price perceptions and postage discounts also influence Muslim consumers' buying interest in the Shopee application.